System and methods for facilitating user- requested content services and related technologies - Stolz, Pascal; Lavista Ferres, Juan M.; Fawthrop, William M.; Etchenique, Andrés Nicolás Charbonier; Mislej, Diego Acosta (US Patent: US20100042592A1, 2010)
Aspects of the invention include a system and a method of providing a scalable system architecture and methods facilitating user-requested content alerts. Additionally, aspects of the invention are directed to a system and method of providing customized alerts to a user link atoms corresponding to discrete subjects of information requested by the user to form molecules which can be received by an interactive media device to display the information corresponding to each atom. Other aspects of the invention include a system and a method of facilitating user-requested content utilizing Real Simple Syndication (RSS). The present invention is further directed at providing a system and method for expanding user-requested content, and systems and methods of facilitating monetization of user-requested content via electronic mail.